Frogs & their habitats : school holidays - Saturday 25 September to Sunday 10 October - Adelaide Zoo ([Adelaide] : Adelaide Zoo, 2010)
Poster advertising frog themed school holiday activities, 25 September-10 October 2010, at the Adelaide Zoo. Features large photographic image of a green tree frog in the lower left corner of the poster, with a smaller red-eyed tree frog appearing on each of the letters in "Frogs" in the title. The Adelaide Zoo website and logo appear at the foot of the poster. A reminder "Don't miss the School Holiday fun at Monarto & Warrawong!" with the logos of each appears over the top of the image of a leaf on the right hand side.
Caption title.
Keywords: Adelaide Zoo -- Posters; Zoos -- South Australia -- Adelaide -- Posters; Frogs -- South Australia -- Adelaide -- Posters; Zoo animals -- South Australia -- Adelaide -- Posters; Posters, Australian; Australia -- Posters; Australian